Effect of Metformin and Valsartan Toward Homa-IR in Metabolic Syndrome Patient with Non-Alcoholic Fatty Liver Disease (NAFLD) - Prasetio Kirmawanto; Siti Nurdjanah; Muhammad Robikhul Ikhsan (Acta Interna The Journal of Internal Medicine, 2017)
ABSTRACTBackground: Insulin sensitizer drugs such as metformin has suggested giving in metabolic syndrome patient and NAFLD, which both pathogeneses were insulin resistance. Angiotensin II receptor blocker (ARB), anti-hypertension drugs, has the similar properties to improve regulation of Proliferator-Activated Receptor Gama (PPARɤ). This aim of the study is to prove the improvement of insulin resistance which examined by HOMA-IR method on metabolic syndrome patient with NAFLD after receiving metformin and valsartan medication.Method: This study was conducted to the patient in Endocrinology Clinic Sardjito General Hospital aged 35-36 years who meet diagnostic criteria for metabolic syndrome based on the IDF in 2006 and NAFLD. Convenience sampling method is done for 11 months (May 2012 – March 2013) and was expected sample size 35. HOMA-IR examination made before and after administration of metformin and valsartan for 12 weeks. Cut off value for HOMA –IR on pathological metabolic syndrome and NAFLD was ≥ 2. Medical and Health Research Ethics Committee (MHREC) Faculty of Medicine Universitas Gadjah Mada approved this study protocol.Result: Subject of study retrieved 15 (43%), six males (40%) and nine females (60%) aged 43-63 years old. Median HOMA-IR baseline was 2.8 (0.6-14.5) and at the end of therapy was 3.8 (1.72-14.1). Eleven (74%) have increased HOMA-IR value and four (26%) experience declined but none of them reach the value below 2. In general clinical improvement occurs in the form of AST and ALT reduction but not statistically significant.Conclusion: This study does not prove that administration of metformin and valsartan in-patient with metabolic syndrome with NAFLD would improve insulin resistance assessed by the HOMA-IR method.Keywords: Metformin, valsartan, metabolic syndrome, NAFLD, HOMA-IR